2015
DOI: 10.1002/hep.27778
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for carbohydrate responsive element binding protein in the control of ethanol metabolism and susceptibility to binge drinking

Abstract: Carbohydrate responsive element binding protein (ChREBP) is central for de novo fatty acid synthesis under physiological conditions and in the context of nonalcoholic fatty liver disease. We explored its contribution to alcohol-induced steatosis in a mouse model of binge drinking as acute ethanol (EtOH) intoxication has become an alarming health problem. Within 6 hours, ChREBP acetylation and its recruitment onto target gene promoters were increased in liver of EtOH-fed mice. Acetylation of ChREBP was dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…that controls transcription of a range of genes involved in free fatty acid transport and oxidation. Recently, it was discovered that the activity ChREBP, an important transcription factor for de novo fatty acid synthesis ( 22 ), is elevated by alcohol exposure ( 24,25 ). In our experimental setting, we found that the mRNA level of ChREBP was not increased by EtOH treatment.…”
Section: Discussionmentioning
confidence: 48%
“…that controls transcription of a range of genes involved in free fatty acid transport and oxidation. Recently, it was discovered that the activity ChREBP, an important transcription factor for de novo fatty acid synthesis ( 22 ), is elevated by alcohol exposure ( 24,25 ). In our experimental setting, we found that the mRNA level of ChREBP was not increased by EtOH treatment.…”
Section: Discussionmentioning
confidence: 48%
“…SREBP‐1c has been implicated as a direct downstream effector of AKT‐mTORC1 signaling in insulin‐induced de novo lipogenesis, whereas ChREBP has been more associated with high carbohydrate feeding, in particular, fructose feeding . A recent study showed loss of Chrebp may sensitize mice from binge‐drinking‐induced liver injury . We observed that L‐pk , the hallmark target of ChREBP, was reduced in the liver of both Bmal1‐LKO and mice with liver specific depletion of Bmal1 but induced in Ad‐ Bmal1 liver (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…ChREBP deficiency in diabetic mice alleviates liver steatosis and improves glucose metabolism (9,10). In addition, ChREBP was found to regulate ethanol metabolism and modulate the degree of ethanol-induced liver injury (11). These studies suggest that ChREBP may regulate liver pathophysiology in a context-dependent manner.…”
Section: Introductionmentioning
confidence: 81%
“…These data highlight the importance of the proper control of UPR and ER stress activity in hepatocytes in the presence of fructose influx and highlight the essential role of ChREBP in maintaining normal liver functions by suppressing the PERK-CHOP branch of the UPR. Recent work from the Postic group demonstrated that ChREBP is important for protecting the liver by regulating ethanol metabolism via sirtuin 1 (SIRT1) (11). It will be interesting to examine the role of the ChREBP-controlled UPR pathway in alcohol-induced liver injury models.…”
Section: A Hfrd Activates the C/ebp Homologous Protein-mediated Apoptmentioning
confidence: 99%